Silage and total mixed ration hygienic quality on commercial farms: implications for animal production. (11th November 2016) - Cogan, T.; Hawkey, R.; Higgie, E.; Lee, M. R. F.; Mee, E.; Parfitt, D.; Raj, J.; Roderick, S.; Walker, N.; Ward, P.; Wilkinson, J. M.
Abstract: Implications of silage hygienic quality for animal production were investigated on forty‐five dairy farms in South West England. Samples of grass and maize silages and of total mixed rations (TMR) were obtained together with information on silage technology, herd size and animal production. Samples were analysed for mycotoxins, bacteria, yeasts, moulds and chemical composition. Thirteen mycotoxins were assayed, but none were detected in the samples of grass silage. However, mycotoxins were found in 0·9 of all maize and other silage samples, with deoxynivalenol and zearalenone predominating. There was no relationship between total mycotoxin concentration and mean lactation milk yield per cow. Enterobacteria counts tended to be higher in maize silage than in grass silage and higher still in TMR – a cause for concern. There were no relationships between mould counts and mycotoxin concentrations in silages, implying that mycotoxins may have been produced in the field pre‐ensiling.